Implementing Design Thinking in Education: The Role of Leadership - OBAIDAT, MARAM (2024)
The study aimed to identify the implementing of design thinking in education: the role of leadership, and the study used the descriptive analytical and correlational approach to suite the purpose of the study. Sample of the study consisted of (210) leaders in the public and private schools which were chosen by random method, while the study based on the questionnaire to collect data from members of the study sample, which has been verified for its validity and reliability. The study showed that the transformational leadership was of a high level as a total among the leaders in public and private schools in UAE and for each dimension in descending order (Idealized influence, Inspirational motivation, social relations, Intellectual stimulation and Individualized consideration) and the study showed that the UAE school principals were implementing design thinking in education with of a high level also. The study also showed that there was a statistically significant role for transformational leadership with its dimensions (Inspiration’s motivation, Intellectual stimulation and social relations) in implementing design thinking in education among school principals in UAE. And the results of the inferential analysis showed that there were no statistically significant differences in the level of implementing design thinking in education among school principals according to the (Gender, Years of experience and educational level). The study recommended the necessity of conducting future studies that address other types of educational leaders, which can affect other variables in the educational field.